DEVELOPMENT OF FLASHCARD LEARNING MEDIA ON THE MATERIAL OF RECOGNIZING FEELINGS IN THE INDONESIAN LANGUAGE SUBJECT IN GRADE II OF ELEMENTARY SCHOOL - Siti Chanifah; Beta Rapita Silalahi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research is motivated by the importance of feelings in elementary school students as part of the development of language and social-emotional skills. The purpose of this study is to develop learning media in the form of flashcards as an aid in learning Indonesian on the material of recognizing feelings for grade 2 elementary school students. Flashcard media is designed to help students recognize and understand various types of feelings through simple and interesting pictures and words. The method used in this study is the research and development method (Research and Development) with the ADDIE model. The development of ADDIE consists of 5 stages, but in this study the researcher carried out the development procedure only up to stage 3, namely (Analysis, Design, and Development). The instrument used to collect data was a questionnaire given to several expert reviewers, namely media expert validators and material expert validators. The development results showed that this flashcard media was very feasible to use based on the assessment of material experts of 86% with the Very Eligible category and media experts of 84% with the Very Eligible category. The use of this media has been shown to increase student involvement in learning and help them recognize and express feelings better. Thus, this flashcard media is very feasible and interesting as a tool in learning Indonesian, especially in recognizing and understanding feelings.